Upaya Meningkatkan Hasil Belajar PAI Melalui Model Pembelajaran Index Card Match (Icm) Kelas IV SDN15 Tarung Tarung Utara - Siagian, Syarifuddin (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This research investigates the effectiveness of the Index Card Match method in improving students' learning outcomes in Islamic Religious Education (PAI) for fourth-grade students at SD Negeri 15 Tarung Tarung Utara. The results from Cycle I and Cycle II show a significant improvement in student performance. In Cycle I, many students were not actively engaged in the learning process, and the learning outcomes did not meet the Minimum Completeness Criteria (KKM). However, Cycle II, with better preparation and clearer instructions, resulted in 75% of students achieving the KKM. Despite this, 25% of students still did not meet the KKM, suggesting that the research should continue into Cycle III to achieve 100% completeness. The application of the Index Card Match method has proven effective in increasing student engagement and learning outcomes, but further development is needed to support students who have not yet met the KKM.